The impact of climate change on land productivity. A micro-level assessment for Italian farms. (February 2023) - Coderoni, Silvia; Pagliacci, Francesco
Abstract: CONTEXT: Both long-term climate trend and interannual climate variability are projected to affect agricultural activities. Actually, major changes in climate patterns have already occurred, affecting crop yields and livestock productivity. OBJECTIVE: This study aims to assess the effects of both interannual temperature and precipitation variability and long-term climate trend on the land productivity of Italian farms. Italy represents an interesting example, as the country is largely affected by the effects of climate change and climate variability, and its agricultural sector shows heterogeneous conditions, including climatic, topographical and socio-economic features. METHODS: The methodological approach considers the effects on land productivity of a set of farm structural and economic characteristics and climate-related variables, by considering farm-level data. A dynamic panel model is estimated via System Generalized Method-of-Moments using a constant panel of 2051 farms observed over the period from 2008 to 2017. Data are extracted from the Italian Farm Accountancy Data Network. RESULTS AND CONCLUSIONS: Results suggest that when coming to farm-level data and addressing the changes in the climate in both the long and the medium term, a negative impact is found on LP because of higher temperatures in the colder seasons and in spring, and because of larger spring cumulative rainfall. On the opposite, wetter summers seem to positively impact LP. As regards Mediterranean regions only a positive impact of larger spring cumulative rainfall is found. Besides, managerial and structural farms' characteristics seem to play a major role in influencing farm performance. SIGNIFICANCE: This study represents a first attempt in the direction of estimating the impact of climate change on farms' land productivity, by using micro-data to prevent aggregation biases and controlling for both managerial and structural farms' characteristics. Graphical abstract: Unlabelled Image Highlights: Globally land productivity is no longer increasing also as a result of climate change. A dynamic panel model is applied to FADN data to assess the impact of climate trend and variability on land productivity. Managerial and structural farms' characteristics play a prominent role in determining land productivity. A negative impact of higher temperatures on land productivity is observed for the cold season and spring. Spring rainfall positively impacts land productivity in the Mediterranean region.